The study on the air pollutants embodied in goods for consumption and trade in China – Accounting and structural decomposition analysis. (1st November 2016) - Deng, Guangyao; Ding, Yufeng; Ren, Suling
Abstract: Recently, comprehensive attention has been attracted to global warming. Meanwhile, China is a country with huge energy consumption and greenhouse gas emission. Therefore, it is urgent for China to reduce the air pollutants embodied in each unit of a good for a less greenhouse gas earth. In this paper, air pollutants embodied in goods consumption as well as import-export trade in China was accounted in 1995–2009. Besides, we checked the structural decomposition analysis of emissions' variation. The results showed: (1) in 1995–2009, air pollutants embodied in goods for consumption and import-export trade in China displayed a rising trend. Emission of carbon dioxide was the largest and methane, carbon monoxide, sulphur oxides, non-methane volatile organic compounds, nitrogen oxides, ammonia, nitrous oxide were in proper sequence based at the average level. (2) Air pollutants embodied in goods exported were larger than those in imported and difference among nations existed. (3) The percentages of carbon dioxide, methane, nitrogen oxides, sulphur oxides, carbon monoxide, non-methane volatile organic compounds embodied in Construction were larger than in other departments on the consumption side, while percentages of carbon dioxide, nitrogen oxides, sulphur oxides, carbon monoxide, non-methane volatile organic compounds embodied in Electrical and Optical Equipment was bigger on the trade side. (4) Emission reduction techniques reduced air pollutants embodied in goods consumption and import and export trade in China. Consequently, China ought to pay attention to emission reduction of carbon dioxide and raise awareness of air pollutants controlling, especially in Construction, Electrical and Optical Equipment and other departments. More importantly, China ought to strengthen cooperation with other nations in emission reduction and developing technologies so as to cut down air pollutants, not only for China but also for the earth. Highlights: China's emissions embodied in goods during 1995–2009 were accounted in this paper. This paper checked the structural decomposition analysis of emissions' variation. Emissions reduction technologies need to be expanded vigorously to make emission down.